Comparative adaptability assessment of bread wheat and synthetic hexaploid genotypes under saline conditions using physiological, biochemical, and genetic indices - Alghabari, Fahad; Shah, Zahid Hussain (Frontiers in Plant Science, 2024)
The tolerance to salinity stress is an intricate phenomenon at cellular and whole plant level that requires the knowledge of contributing physiological and biochemical processes, and the genetic control of participating traits. In this context present study was conducted with objective to evaluate the physiological, biochemical and genetic responses of different wheat genotypes including bread wheat (BW) and synthetic hexaploids (SH) under saline and control environment. The experiment was conducted in two factorial arrangement in randomized complete block design (RCBD), with genotypes as one factor and treatments as another factor. A significant decline in physiological traits (chlorophyll, photosynthesis, stomatal conductance, transpiration, cell membrane stability) was observed in all genotypes due to salt stress, however this decline was higher in BW genotypes as compared to four SH genotypes. Besides, the biochemical traits including enzymes (superoxide dismutase, catalase, peroxidase) activity, proline and glycine betaine (GB) illustrated significant increase along with increase in the expression of corresponding genes (TaCAT1, TaSOD, TaPRX2A, TaP5CS, and TaBADH-A1) due to salt stress in SHs as compared to BW. Correspondingly, highly overexpressed genes, TaHKT1;4, TaNHX1 and TaAKT1 caused a significant decline in Na + /K + in SH as compared to BW genotypes under salt stress. Moreover, correlation analysis, principal component analysis (PCA), and heatmap analysis have further confirmed that the association and expression of physiological and biochemical traits varied significantly with salinity stress and type of genotype. Overall, the physiological, biochemical and genetic evaluation proved SHs as the most useful stock for transferring salinity tolerance to other superior bread wheat cultivars via the right breeding program.